ANALISIS PENGARUH PDB, KONSUMSI BATUBARA, PMA, URBAN DAN KONSUMSI ENERGI TERHADAP CO2 DI NEGARANEGARA ASEAN 2000-2011 - Samuel Handy Wijaya (CALYPTRA, 2017)
Abstract -This study is aims to determine the influence of GDP, the Consumption of Coal, Foreign Direct Investment, Urbanization and Energy Consumption to CO2 in the ASEAN countries from 2000 to 2011. This study uses a quantitative approach using regression model analysis. This study uses a sample of six ASEAN member countries, namely Indonesia, Vietnam, Thailand, Malaysia, Singapore, and the Philippines for the period 2000-2011. The research finds that there is a positive relation between the GDP, coal consumption, urbanization and energy consumption to CO2 , while foreign direct investment has no relation to CO2 . The result is expected to contribute on SDG achievement. The result contribute to the development of environmental economics as well as the strategy to promote SDG. Keywords: CO2, GDP, Consumption of Coal, Foreign Direct Investment, Urbanization, Energy Consumption